Evaluation of crack width predictions in Eurocode 2 using Digital Image Correlation - SMEREKA, PRZEMYSLAW (My University, 2019)
ABSTRACT A correct prediction of crack widths in reinforced concrete elements in Serviceability Limit State (SLS) is important in terms of keeping the proper functionality of the structure. The purpose of this thesis was to investigate the accuracy of crack width predictions using Eurocode 2 (EC 2) and ACI 224R compared with three-point bending tests on simply supported reinforced concrete beams. The crack widths were measured using normal speed cameras recording at a rate of 0.5 frames per second (fps). Later on, the data was processed using Digital Image Correlation (DIC). A strain field of the studied beam has been created using the 3D software GOM Correlate Professional. The crack widths were measured by creating two facet points per each crack directly at the level of bottom reinforcement. Horizontal displacements between these points were calculated giving a precise value of crack widths which appeared in the cracked cross-sections of reinforced concrete beams. Corresponding reinforcement stresses in cracked cross-sections were calculated and plotted in a stress-crack width relation, together with the theoretical values coming from EC 2 and ACI 224R. The direct location of the cracks was measured using two different reference points using DIC. The accuracy for the measured crack spacing was estimated to ±5 mm and for crack widths estimated to ±0.01 mm. As expected, the largest cracks appeared in the middle section of the beam where the cross-sectional stresses are the highest. The results show that the maximum crack spacing and the mean value of crack spacing is accurately predicted by EC 2. Furthermore, EC 2 gives a quite good estimation for the mean values of crack widths whereas ACI 224R seems to overestimate the mean crack widths. When comparing the maximum crack widths, it can be observed that EC 2 gives a very precise prediction which corresponds with DIC results. However, in some of the cases especially in the beginning stage of crack propagation it can be noted that both EC 2 and ACI 224R overestimates the crack widths.
Keywords: Digital Image; DIC; reinforced concrete; Correlation; simply supported; beams; static loading; Eurocode 2; ACI 244R; GOM Correlate; 30Professional; crack widths; crack pacing; Serviceability Limit State; SLS